2020
DOI: 10.3390/microorganisms8071044
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbohydrate Tolerant LAB Strains Identified from Rumen Fluid: Investigation of Probiotic Activity and Legume Silage Fermentation

Abstract: The objective of this study was to isolate and characterize lactic acid bacteria (LAB) with low carbohydrate tolerance from rumen fluid and to elucidate their probiotic properties and the quality of fermentation of Medicago sativa L. and Trifolium incarnatum L. silage in vitro. We isolated 39 LAB strains and screened for growth in MRS broth and a low-carbohydrate supplemented medium; among them, two strains, Lactiplantibacillus plantarum (Lactobacillus plantarum) RJ1 and Pediococcus pentosaceus S22, were able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…Isolated from rumen fluid, P. pentosaceus S22, with low carbohydrate tolerance, exhibited good adaptability to the gastric juice environment. Research showed that P. pentosaceus S22 greatly improved the quality of fermentation of legume silage in vitro [ 70 ]. Eveno et al [ 71 ] proposed that P. pentosaceus ICVB491 produced bacteriocins and biofilms with low pathogenic risks and high compatibility.…”
Section: Evidence Of P Pentosaceus Use In Food Enmentioning
confidence: 99%
“…Isolated from rumen fluid, P. pentosaceus S22, with low carbohydrate tolerance, exhibited good adaptability to the gastric juice environment. Research showed that P. pentosaceus S22 greatly improved the quality of fermentation of legume silage in vitro [ 70 ]. Eveno et al [ 71 ] proposed that P. pentosaceus ICVB491 produced bacteriocins and biofilms with low pathogenic risks and high compatibility.…”
Section: Evidence Of P Pentosaceus Use In Food Enmentioning
confidence: 99%
“…The current practice of silage-making combines several LAB strains [61][62][63][64][65] to induce silage fermentation (alfalfa, legumes, maize, grains, meadow, etc.) through a synergistic action, thus enhancing the stability for more than one year of storage [66].…”
Section: Natural Additives For Silage Productionmentioning
confidence: 99%
“…Based on the previous studies, in vitro assessments, such as acid, bile and pancreatic enzymes tolerance, and survey some physiological characteristics (such as optimum growth temperature and salt sensitivity) have been considered as a good indicator to evaluate the probiotic properties of a bacterial isolates (Kim et al 2019;Kuppusamy et al 2020). After preliminary growth assays under acidic condition, seventy LAB isolates exhibited good survivability to pH ¼ 3 (data not shown).…”
Section: Survival Assays Under Acidic Conditions Bile Salts and Pancreatin Resistancementioning
confidence: 99%
“…Lactic acid bacteria (LAB) have been used as probiotics to modulate the composition of intestinal microbiota to promote the health of the host intestine (de Moraes et al 2017). LAB isolates have been isolated from a variety of sources, including fermented and dairy products, plants, soil and various organs of poultry, cattle or fish (Kuppusamy et al 2020). In addition, large amounts of LAB with vital function have been found in the ruminant's digestive tract (Timmerman et al 2006).…”
Section: Introductionmentioning
confidence: 99%